MASCULINITIES IN STUDENT POLITICS: GENDERED DISCOURSES OF STRUGGLE AND LIBERATION AT THE UNIVERSITY OF LIMPOPO - Oxlund, Bjarke (PINS-Psychology in Society, 2025)
The article examines the role of discourses of struggle and liberation in the performance of gender in student politics at the University of Limpopo. Moving from an understanding of how discourses of masculinity intertwine with the discourses of student activism and the struggle against apartheid, the article analyses the elections held for the Students’ Representatives Council (SRC) at Turfloop Campus in October 2006. It is argued that male student politicians draw on struggle history and revocations of African traditionalism in ways that keep them at the centre of student politics, while female students are kept on the margins as a muted group. The article aims to show how male and female students position themselves as gendered beings in the realm of student politics; and how, in the process, discourses of gender and the struggle translate into social practice. The analysis shows that it is not fruitful to view discourses of gender in isolation from other discourses. Rather, the reading of the student elections points to the need for a careful examination of how discourses of gender are entangled in broader discourses of hegemony at the political level; and not least how organisations and individual actors engage with these discourses.